2012
DOI: 10.1002/dvg.22030
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of a Notch1 signaling‐specific reporter mouse line

Abstract: Signaling through the Notch1 receptor is essential for the control of numerous developmental processes during embryonic life as well as in adult tissue homeostasis and disease. Since the outcome of Notch1 signaling is highly context‐dependent, and its precise physiological and pathological role in many organs is unclear, it is of great interest to localize and identify the cells that receive active Notch1 signals in vivo. Here, we report the generation and characterization of a BAC‐transgenic mouse line, N1‐Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Notch components, although broadly expressed throughout brain tissue, are also found in cells of the SVZ and the SGZ, suggesting that Notch might regulate postnatal NSCs (Stump et al, 2002;Irvin et al, 2004;Givogri et al, 2006). Consistent with this possibility, Notch activity was detected in postnatal or adult NSCs using different reporter mice (Ehm et al, 2010;Imayoshi et al, 2010;Lugert et al, 2010;Smith et al, 2012). Conditional gain-and loss-of-function studies demonstrated that Notch regulates quiescence and cell cycle exit of NSCs.…”
Section: Notch: a Key Regulator Of Adult Nscsmentioning
confidence: 93%
“…Notch components, although broadly expressed throughout brain tissue, are also found in cells of the SVZ and the SGZ, suggesting that Notch might regulate postnatal NSCs (Stump et al, 2002;Irvin et al, 2004;Givogri et al, 2006). Consistent with this possibility, Notch activity was detected in postnatal or adult NSCs using different reporter mice (Ehm et al, 2010;Imayoshi et al, 2010;Lugert et al, 2010;Smith et al, 2012). Conditional gain-and loss-of-function studies demonstrated that Notch regulates quiescence and cell cycle exit of NSCs.…”
Section: Notch: a Key Regulator Of Adult Nscsmentioning
confidence: 93%
“…The line, currently named N1::Cre LO (but referred to in the original publication as N 1 IP-Cre , for N otch 1 I ntramembrane P roteolysis- Cre ), when crossed with a Cre reporter such as the ROSA26R strain (53), permits in vivo mapping of Notch1 activation by gamma secretase-mediated proteolytic cleavage. While not a Notch receptor-Cre fusion, Radtke and colleagues have developed a conceptually similar bi-transgenic Notch1 reporter system (54). They constructed a bacterial artificial chromosome (BAC) transgenic line ( N1-Gal4VP16 ) containing a modified Notch1 cDNA, in which the intracellular domain of the Notch1 receptor was replaced with sequence encoding the Gal4VP16 transcriptional activator.…”
Section: Notch Receptor-cre Fusions For Fate Mapping and Functionamentioning
confidence: 99%
“…They constructed a bacterial artificial chromosome (BAC) transgenic line ( N1-Gal4VP16 ) containing a modified Notch1 cDNA, in which the intracellular domain of the Notch1 receptor was replaced with sequence encoding the Gal4VP16 transcriptional activator. When crossed to a transgenic Gal4 reporter line, such as UAS-lacZ mice (55), the N1-Gal4VP16 line permits the identification in vivo of cells undergoing active Notch1 signaling (54). …”
Section: Notch Receptor-cre Fusions For Fate Mapping and Functionamentioning
confidence: 99%
“…This characteristic of receptor cleavage enables the specific labeling of ligand-receptor binding by replacing NICD with the yeast transcription factor Gal4 and herpes simplex virus protein VP16 [ 6 ]. In this study, we generated a new transgenic mouse line that expressed Cre recombinase and a near-infrared fluorescent protein, miRFP670 (UAS-Cre-T2A-miRFP670, UC2i), and examined whether this transgenic mouse line is applicable in labeling protein-protein interaction by using Notch1-Gal4VP16 expressing transgenic mouse line (N1-Gal4VP16) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic of receptor cleavage enables the specific labeling of ligand-receptor binding by replacing NICD with the yeast transcription factor Gal4 and herpes simplex virus protein VP16 [ 6 ]. In this study, we generated a new transgenic mouse line that expressed Cre recombinase and a near-infrared fluorescent protein, miRFP670 (UAS-Cre-T2A-miRFP670, UC2i), and examined whether this transgenic mouse line is applicable in labeling protein-protein interaction by using Notch1-Gal4VP16 expressing transgenic mouse line (N1-Gal4VP16) [ 6 ]. This strategy would enable labeling the past and ongoing Notch1 activity at a cellular level, using another previously established transgenic mouse line (R26GRR) that expressed EGFP and tandem dsRed before and after Cre recombinase-mediated recombination under regulation of the chicken actin gene (CAG) promotor inserted in the ROSA26 locus [ 7 ].…”
Section: Introductionmentioning
confidence: 99%